Thermodynamic and spectroscopic studies of Cd²⁺ binding to the regulatory domain and full length human cardiac troponin C (HcTnC) : elucidating plausible Cd²⁺ binding sites - Fulcher, Lindsay Michelle (East Carolina University, 2015)
Toxic metals such as cadmium (Cd²⁺) have been shown to bind to and interfere with various calcium (Ca²⁺) binding proteins including the regulatory protein cardiac troponin C (cTnC). Recent structural data has shown that Cd²⁺ binds to both EF hand Ca²⁺ binding loops in the regulatory N-domain of human cTnC including EF hand loop I, which normally does not bind metal. Although the data reveal two Cd²⁺ ions bound to the protein, the binding constants and other thermodynamic parameters are not known. Therefore, the goal of this research project is to use Isothermal Titration Calorimetry (ITC) to obtain thermodynamic parameters such as K, [delta]H, [delta]G and [delta]S of Cd²⁺ binding to both the full length and N-domain (amino acid residues 1-89) of HcTnC and compare the parameters to our previous data with Ca²⁺. Through our results we hope to shed light on potential mechanisms of cadmium toxicity.
Keywords: Biochemistry; Inorganic chemistry; Bioinorganic chemistry; Circular dichroism; EF hands; HcTnC; Isothermal titration calorimetry; Toxic metals; Cadmium--Isotopes; Calcium--Isotopes; Heavy metals; Calcium-binding proteins; Calorimetry